Advanced near‐infrared light‐responsive nanomaterials as therapeutic platforms for cancer therapy - Chien, Yi-Hsin (2020)
Cancer is one of the leading causes of death. Despite the huge progress in the field of cancer drugs and therapies, the treatment outcome is still bleak for most cancer patients. Nanotechnology has revolutionized cancer therapeutics. By using nano‐sized particles as delivery systems, therapeutic biomolecules are transported efficiently to the target sites. Moreover, these particles are designed to carry out multiple cancer treatments simultaneously. Near‐infrared (NIR) light‐responsive nanomaterials have gained much attention as NIR light has a greater penetration depth, minimal phototoxicity, lower autofluorescence, and reduced light scattering. Among the available NIR light‐responsive nanomaterials, gold nanorods, upconversion nanoparticles, carbon dots, transition metal dichalcogenide, metal oxides, black phosphorus, and polymeric nanomaterials have become attractive options owing to their excellent optical properties, ease of synthesis and modification, outstanding photodynamic and photothermal conversion properties, and most importantly, favorable toxicity level and biocompatibility which are prerequisites for biological applications. In this review, the outstanding properties, synthesis, and surface functionalization of the aforementioned NIR light‐responsive nanomaterials are introduced in detail. Recent advances of these nanomaterials for various cancer treatment modalities are summarized to highlight their versatility and potential in cancer theranostics. Finally, a perspective is proposed on future research directions and their clinical translation.